The Effect of Intrapersonal Communication, Religious Content, and Understanding of Religious Moderation Values on the Spiritual Behavior of Virgo Fidelis Senior High School Students in Bawen - Putro, Adi Nugroho Susanto; Setyoko, Rahmad; Purnomo, Danang Try; Putranto, Dwiyono (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the influence of interpersonal communication, religious content, and understanding of religious moderation values on students' spiritual behavior. This study was conducted using a quantitative research method. The subjects of this study were students of SMA Virgo Fidelis Bawen with a sample of 99 students. Data were collected through a questionnaire with a Likert scale of 1-5. The results of the validity and reliability tests of the instrument showed that the instruments used in this study were valid and reliable. Data were analyzed using descriptive statistical analysis and regression analysis. The normality test showed that the data on the four research variables were normally distributed. The multicollinearity test showed that there were no symptoms of multicollinearity in the independent variables. The heteroscedasticity test showed that the distribution of points on the scatter plot did not have a clear pattern so that it could be interpreted that there was no heteroscedasticity. Thus, all the requirements for regression analysis were met. The results showed that intrapersonal communication had a significant effect on students' spiritual behavior with a coefficient of determination (R2) of 0.488 (sig. 0.000). Religious content has a significant effect on students' spiritual behavior with a coefficient of determination (R2) of 0.585 (sig. 0.000). Understanding of religious moderation has a significant effect on students' spiritual behavior with a coefficient of determination (R2) of 0.821 (sig. 0.000). Intrapersonal communication, religious content, and understanding of religious moderation are proven to have a significant simultaneous effect on students' spiritual behavior. This is indicated by the results of the F-test of 194.393 with a significance of 0.000. Intrapersonal communication has an effective contribution (SE) of 4% and a relative contribution (SR) of 5%, religious content has an effective contribution (SE) of 15% and a relative contribution (SR) of 17%, while understanding of religious moderation has an effective contribution (SE) of 55% and a relative contribution (SR) of 64%. The equation of the regression line formed is Y = 0.080X1 + 0.948X2 + 0.700X3 – 25.547.